A Sensemaking Approach to Europe’s Data Strategy - Polyviou, Ariana (My University, 2022)
The use of data-driven tools provides a plethora of benefits and chal- lenges from a data policy-making perspective. This holds implications at organ- izational, national, and regional levels. At regional level the development of high- quality data-driven tools, among others, involve geo-political implications as they contribute to the region’s competitive advantage. In Europe, the European Commission has made attempts towards the formulation of a regional policy on data, aiming at fostering Europe’s global competitiveness and data sovereignty. Despite its geo-political impact, academic research on data strategy formulation at regional level remains scarce. While existing IS scholars have largely empha- sized on data strategies, the focus of these studies has been mainly at organiza- tional level. This paper motivates the need to go beyond data policies the organ- izational level and deepen our understanding on how data policies are formulated at regional level. Focusing on the case of the European regional area and the Eu- ropean Data Act formulation, the proposed research aims to shed light on how stakeholders make sense of the forthcoming data policy in Europe. The paper reflects on existing literature on data governance and availability and discusses its relevance to data policy formulation at regional level. It proposes sensemaking as a theoretical lens for this research and describes the methodology for the pro- posed research.